2018
DOI: 10.3389/fmicb.2018.00460
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Induces Hepatocyte Apoptosis via Mitochondrial Pathway in Mongolian Gerbils

Abstract: Previous studies demonstrated that Mongolian gerbils can be infected by hepatitis E virus (HEV), which induces the hepatic injury. Here, the mitochondria in hepatocytes from HEV-infected gerbils were considerably swollen, thin cristae. After HEV infection, the activity of superoxide dismutase significantly decreased (p < 0.01), while malondialdehyde concentrations significantly increased, compared with those in the control group (p < 0.01). Adenosine triphosphatase levels decreased significantly in the hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
10
2
Order By: Relevance
“…The steady state of pro-survival Bcl-2 members could also be destroyed after the activation of Bak and Bax (McArthur et al, 2018). The previous study has shown that HEV infection led to mitochondria-mediated apoptosis of hepatocytes, such as induction of Bax, Bcl-2, caspase-9, and caspase-3 (Yang et al, 2018). In our study, increased TUNEL-positive signals were observed in infected brain tissues.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The steady state of pro-survival Bcl-2 members could also be destroyed after the activation of Bak and Bax (McArthur et al, 2018). The previous study has shown that HEV infection led to mitochondria-mediated apoptosis of hepatocytes, such as induction of Bax, Bcl-2, caspase-9, and caspase-3 (Yang et al, 2018). In our study, increased TUNEL-positive signals were observed in infected brain tissues.…”
Section: Discussionsupporting
confidence: 70%
“…It has been reported that the release of cytochrome c was increased in BHK-21 cells infected with bovine ephemeral fever virus (BEFV) and activation of caspase-9, as well as the downstream effector caspase-3, were further detected (Lin et al, 2009). In gerbil model of HEV infection, mitochondrial damages such as mitochondria swelling, devoid of mitochondrial cristae were observed in hepatocytes via transmission electron microscope (TEM) (Yang et al, 2018). In Yang's study, up-regulation of mitochondria-mediated apoptosis regulating proteins, Bax and Bcl-2, in HEV-infected gerbils, as well as induction of activated caspase-9 and caspase-3 were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information of transcription system for RNA and amplifying system for HEV RNA RT-PCR are listed in Supplementary Tables S1 , S2 . Amplification conditions for both round of PCR were: 94°C for 3 min; 30 cycles of 94°C for 30 s, 58°C for 35 s, and 72°C for 30 s; 72°C for 7 min ( Yang et al, 2018 ). Negative (pure water) and positive (HEV RNA) controls were designed in the RT-PCR assay.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining was performed following the instructions that were included in the Histostain TM -Plus kit (ZSGB-BIO, Beijing, China). 3,3′-Diaminobenzidine tetrahydrochloride (DAB; ZSGB-BIO, Beijing, China) was applied for 5 min to visualize the antigen–antibody compound, Gill’s hematoxylin was applied as the background stain ( Yang et al, 2018 ). The slides were observed under light microscope (Olympus Optical Co., Ltd., Beijing, China) and positive signals for HEV-ORF2 proteins were represented by a brown or yellow granular mass ( Soomro et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, HCV infection enhances susceptibility to Fas‐mediated apoptosis, whereas several HCV proteins (core, E1, E2, and NS proteins) inhibit TNF‐α‐mediated apoptosis . Recently, HEV has been reported to induce hepatocyte apoptosis via mitochondrial pathway in Mongolian gerbils . However, the underlining interaction between apoptosis and HEV infection remains largely obscure.…”
Section: The Mutual Interactions Between Hepatitis Viruses and Mitochmentioning
confidence: 99%